Four-Neutrino Analysis of 1.5 km Baseline Reactor Antineutrino Oscillations - Sin Kyu Kang; Yeong-Duk Kim; Young-Ju Ko; Kim Siyeon (Advances in High Energy Physics)
The masses of sterile neutrinos are not yet known, and depending on the orders of magnitudes, their existence may explain reactor anomalies or the spectral shape of reactor neutrino events at 1.5 km baseline detector. Here, we present four-neutrino analysis of the results announced by RENO and Daya Bay, which performed the definitive measurements of θ13 based on the disappearance of reactor antineutrinos at km order baselines. Our results using 3 + 1 scheme include the exclusion curve of Δm412 versus θ14 and the adjustment of θ13 due to correlation with θ14. The value of θ13 obtained by RENO and Daya Bay with a three-neutrino oscillation analysis is included in the 1σ interval of θ13 allowed by our four-neutrino analysis.